The struggle to accept unique gender identity in the life of an intersex person in "None of the Above" by I.W. Gregorio - Asmarani, Ratna (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
Considering that the issue of sex and gender is getting more and more complicated, the aim of this paper is to deal with the struggle to accept unique gender identity faced by a young female main character with intersex condition as depicted in the novel entitled None of the Above (2015) written by I.W. Gregorio. To support the analysis certain concepts are borrowed. Based on the complicated and nonlinear relation between sex and gender as detected by Butler, the focus is on the notion of intersex condition, the medical awareness of intersex condition, the meaning of intersex condition, the proposed medical solution for intersex person, and a specific intersex condition called AIS. The research methods used to support the analysis are a combination of library research method, qualitative research method, and contextual research method in the research frame of feminist literary criticism. The results shows that even in the modern world, a person with intersex condition is still considered as a freak who has to struggle painfully, bitterly, and traumatically to understand, overcome, and finally accept her condition. Understanding and support from medical circle, family and close relative, and some open-minded people, help the young intersex female gain her life back as a female whatever her chromosome is.